L3 Populations in Laying Hens Infected with 6,000 L2 of Ascaridia galli - D, Darmawi; Balqis, Ummu; Tiuria, Risa; Soejoedono, Retno D.; Pasaribu, Fachriyan H. (Universitas Syiah Kuala, 2007)
The aim of the present study was to determine the survival of L3 populations in intestine ofchickens exposed to experimental Ascaridia galli infection. Nature female adult worm were obtained fromlumen of village chickens in a comercial abattoir in Bogor. The eggs (L1) obtained from uteri female adultworms were incubated in sterile aquadestilata at room temperature for 10-20 days developed embrionatedeggs (L2). Five groups (A-D) of 80 head chickens were infected with, 6000 L2 A. galli respectively. Thechickens of group A were infected six times with dose of each 1,000 L2 with an interval of one hour. Thechickens of group B were infected three times with dose of each 2,000 L2 with an interval of two hours.The chickens of group C were infected six times with dose of each 3,000 L2 with an interval of three hours. The chickens of group D were infected one time with single dose 6,000 L2. A. galli L3 were recovered from intestines of 80 heads chickens seven days after oesophagus inoculation with 6,000 L2.The result showed that total 702,000 L1 and 628,000 L2 collected from 124 A. galli female adult worms.The percentage of L1 developed L2 is 89.46% and L2 developed L3 is 11.27%. Significant survival of L3higher populations in intestine of chickens observed only in the group D. The results indicated thatchickens infected high dose of A. galli caused the decrease of host defence against ascaridiosis. Keywords: Ascaridia galli, embrionated eggs, larvae